Nijmegen Breakage Sendromu; Farklı Fenotipte İki Kardeş - (:unkn) unknown (My University, 2016)
Nijmegen Breakage sendromu (NBS); kromozomal instabilite, kombine immün yetmezlik ve ayırd edici fiziksel özelliklerle karakterizedir. Burada farklı klinik belirtiler gösteren iki kardeş sunulmaktadır. İndeks olgu olan 6 yaşında kız hastada boy kısalığı, mikrosefali, hepatosplenomegali, rektovajinal fistül, anal atrezi, ektopik böbrek, tekrarlayan ateş ve otit mevcuttu. Yedi yaşında erkek kardeşinde ise tekrarlayan enfeksiyon öyküsü olmaksızın gelişme geriliği, nöromotor gerilik ve mikrosefali saptandı. Her iki kardeşte de hipogammaglobulinemi, B hücre lenfopenisi ve fitohemaglütinin ile lenfosit proliferasyon yanıtında azalma gözlendi. Her iki hastada NBN (NBS1) geninde homozigot c.657_661delACAAA (p.Lys219Asnfs*16) mutasyonu saptandı.

The Nijmegen Breakage syndrome (NBS) is characterized by chromosomal instability, combined immunodeficiency, and distinctive physical features. We present two siblings with NBS presenting with strikingly different manifestations. The proband is a 6-year-old female with short stature, microcephaly, hepatosplenomegaly, rectovaginal fistula, anal atresia, an ectopic kidney, recurrent fevers and otitis media. A 7-year-old brother has developmental delay, failure to thrive, and microcephaly without recurring infections. Both patients have hypogammaglobulinemia, B cell lymphopenia and reduced phytohaemagglutinin-induced lymphocyte proliferation. Both siblings are homozygous for the c.657_661delACAAA (p.Lys219Asnfs*16) mutation in the NBN (NBS1) gene.
Nijmegen-Breakage Syndrome; Two Siblings Presenting with Different Phenotypes
Keywords: Pediatri